KAPASITAS BPBD KABUPATEN BLORA DALAM PENANGGULANGAN BENCANA DAERAH - Ega Elyana; Aufarul Marom (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Blora is one of the areas in Central Java which is prone to disaster area. Potential disasters that may occur in Blora are drought, floods, landslides, whirlwinds and fires. This study aims to describe how the capacity of The Regional Disaster Relief Agency (BPBD) of Blora in regional disaster management area and know the constraints that exist in BPBD Blora in disaster management. This research use qualitative method, data source used is primary data and secondary data. The data will be analyzed by descriptive analysis method. The theoretical basis used is the theory of capacity assessment by Patton & Sawicky. Based on the analysis, it was found that The Regional Disaster Relief Agency (BPBD) of Blora deficient in terms of supporting infrastructure for disaster relief and infrastructure that is already available is need for rejuvenation, there is no human resources qualified in the field of disaster, there is no early warning system or often called the early warning system (EWS), which serves to provide warning of the hazard.